Answer:
48
Step-by-step explanation:
80/100=0.8
0.8x60=48
Answer: ![P(B|A)=\dfrac{4}{9}](https://tex.z-dn.net/?f=P%28B%7CA%29%3D%5Cdfrac%7B4%7D%7B9%7D)
Step-by-step explanation:
Given: A bag contains 2 black balls, 4 yellow balls and 4 white balls.
Event A is defined as drawing a white ball on the first draw.
Event B is defined as drawing a black ball on the second draw.
P(B|A) is expressed as the conditional probability of occurring B given that A.
i.e. it is the probability of happening B where A is already happended.
If a white ball is drawn at first, then the number of black ball(4) remains unchanged but the total number of balls (10) will become 9.
![Probability=\dfrac{Number\ of \ favorable \ outcomes}{Total\ outcomes}](https://tex.z-dn.net/?f=Probability%3D%5Cdfrac%7BNumber%5C%20of%20%5C%20favorable%20%5C%20outcomes%7D%7BTotal%5C%20outcomes%7D)
Then, ![P(B|A)=\dfrac{4}{9}](https://tex.z-dn.net/?f=P%28B%7CA%29%3D%5Cdfrac%7B4%7D%7B9%7D)
3x - (2x + 8) = -6
3x -2x - 8 = -6
x - 8 = -6
x - 8 + 8 = -6 + 8
x = 2
The question is an illustration of arithmetic operations.
The integer that represents the vertical rise is 76
<em>Upward movements are represented with positive, while downward movements are represented with negative.</em>
<em />
So, the given parameters are:
![Up = 100m](https://tex.z-dn.net/?f=Up%20%3D%20100m)
![Down = -72m](https://tex.z-dn.net/?f=Down%20%3D%20-72m)
![Up= 48m](https://tex.z-dn.net/?f=Up%3D%2048m)
The vertical rise is:
![Rise = Up_1 + Down + Up_2](https://tex.z-dn.net/?f=Rise%20%3D%20Up_1%20%2B%20Down%20%2B%20Up_2)
So, we have:
![Rise = 100m -72m +48m](https://tex.z-dn.net/?f=Rise%20%3D%20100m%20-72m%20%2B48m)
![Rise = 76m](https://tex.z-dn.net/?f=Rise%20%3D%2076m)
Hence, the integer that represents the vertical rise is 76
Read more about arithmetic operations at:
brainly.com/question/15385899
f^3+11g-4hf 3 +11g−4hf, cubed, plus, 11, g, minus, 4, h when f=3f=3f, equals, 3, g=2g=2g, equals, 2 and h=7h=7h, equals, 7.
Alik [6]
Given:
The expression is:
![f^3+11g-4h](https://tex.z-dn.net/?f=f%5E3%2B11g-4h)
The given values are
.
To find:
The value of the given expression for the given values.
Solution:
We have,
![f^3+11g-4h](https://tex.z-dn.net/?f=f%5E3%2B11g-4h)
After substituting
, we get
![f^3+11g-4h=(3)^3+11(2)-4(7)](https://tex.z-dn.net/?f=f%5E3%2B11g-4h%3D%283%29%5E3%2B11%282%29-4%287%29)
![f^3+11g-4h=27+22-28](https://tex.z-dn.net/?f=f%5E3%2B11g-4h%3D27%2B22-28)
![f^3+11g-4h=49-28](https://tex.z-dn.net/?f=f%5E3%2B11g-4h%3D49-28)
![f^3+11g-4h=21](https://tex.z-dn.net/?f=f%5E3%2B11g-4h%3D21)
Therefore, the value of the given expression is 21.